2021
DOI: 10.1017/s1041610220004007
|View full text |Cite
|
Sign up to set email alerts
|

Semantic intrusion errors as a function of age, amyloid, and volumetric loss: a confirmatory path analysis

Abstract: Objective: To examine the direct and indirect effects of age, APOE ϵ4 genotype, amyloid positivity, and volumetric reductions in AD-prone brain regions as it relates to semantic intrusion errors reflecting proactive semantic interference (PSI) and the failure to recover from proactive semantic interference (frPSI) on the Loewenstein-Acevedo Scales of Semantic Interference and Learning (LASSI-L), a cognitive stress test that has been consistently more predictive of preclinical and prodromal Alzheimer’s dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Among patients with aMCI, tests utilizing frPSI and semantic intrusions have been shown to better discriminate between those who are amyloid positive versus amyloid negative than the number of correct responses on frPSI ( Curiel et al, 2018b ; Loewenstein et al, 2018b ; Kitaigorodsky et al, 2021 ; Zheng et al, 2021 ). On the other hand, among cognitively unimpaired older adults, the number of correct responses on frPSI have been shown to be very sensitive predictors of progression to PreMCI and aMCI independent of etiology ( Curiel et al, 2018a ; Crocco et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with aMCI, tests utilizing frPSI and semantic intrusions have been shown to better discriminate between those who are amyloid positive versus amyloid negative than the number of correct responses on frPSI ( Curiel et al, 2018b ; Loewenstein et al, 2018b ; Kitaigorodsky et al, 2021 ; Zheng et al, 2021 ). On the other hand, among cognitively unimpaired older adults, the number of correct responses on frPSI have been shown to be very sensitive predictors of progression to PreMCI and aMCI independent of etiology ( Curiel et al, 2018a ; Crocco et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dissociation between correct responses on LASSI-L and semantic intrusion errors caused us to reflect on how PSI and frPSI might represent different cognitive processes in AD. Using confirmatory path analysis, (Zheng et al, 2021) found that among 212 participants, semantic intrusion errors on both Cued B1 and Cued B2 of the LASSI-L were related to both amyloid positivity and decreased brain volumes on MRI using a composite of AD-prone regions (Dickerson et al, 2011). Apolipoprotein E ε4 status exerted indirect effects through its relationship with amyloid positivity while increased age also exerted its effects indirectly through both amyloid positivity and volumetric reductions.…”
Section: Psi Frpsi and Semantic Intrusion Errorsmentioning
confidence: 99%
“…A growing body of evidence indicates that maximum learning of the initial targets, PSI, frPSI and semantic intrusion errors on the LASSI-L are very sensitive in discriminating between older adults who are cognitively healthy and those with PreMCI or MCI due to AD with amyloid PET biomarker positivity [ 12 ] [ 14 ] [ 15 ] [ 16 ]. Multiple studies highlighted that LASSI-L deficits, particularly frPSI, are related to volumetric reductions in AD-prone brain regions [ 12 ] [ 17 ] [ 18 ] [ 19 ]. Further, even in cognitively unimpaired older adults with otherwise normal performance on a traditional neuropsychological battery, these AD-salient cognitive deficits were also associated with increased amyloid load in AD-prone areas [ 11 ].…”
Section: Introductionmentioning
confidence: 99%